The complete chloroplast genome of Schizonepeta tenuifolia (Benth.) Briq., a traditional Chinese herb - Hanping Wang; Yan Wang; Huyin Cheng; Mengju Xue; Jinpei Wang; Zhiyong Yue (Mitochondrial DNA. Part B. Resources, 2021)
Schizonepeta tenuifolia (Benth.) Briq. is a traditional Chinese medicinal herb. The complete chloroplast genome sequence of S. tenuifolia was obtained by high-throughput sequencing platform. The chloroplast genome of S. tenuifolia is a circular form of 151,254 bp in length, with an average GC content of 37.85%. The genome contains a set of 132 genes, including 87 protein-coding genes, 37 tRNA genes, and eight rRNA genes. Phylogenetic analysis based on complete chloroplast genome sequences indicates that S. tenuifolia has a close relationship with Dracocephalum palmatum. This study provides a molecular basis for the classification of S. tenuifolia.